Detection of Human Herpes Virus-6 in saliva of Patients with Bell's palsy - Mustafa Hameed Majeed; Abdul–Kareem Kadhim Alkhazraji (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2022)
Background: Bell’s palsy is unilateral peripheral paralysis of the seventh cranial nerve, several mechanisms have been proposed in the pathogenesis of this disease, among the viral infections specially herpes virus's family including roseola viruses that have been detected in patients' saliva.